Circular RNA circLIMK1-005 promotes the progression of lung adenocarcinoma by interacting with RPA1 protein to activate CDK4 signaling - Xia Yang; Lu Liu; Zhongjian Yu; Yuanlin Chen; Shiting Xu; Meiyuan Liu; Meng Wang; Huili Guo; Zhiwu Zhang; Bingjie Shan; Silin Cai; Mengting Pan; et al. (Cell Death Discovery)
Abstract Lung adenocarcinoma (LUAD) is the leading cause of cancer death worldwide. Circular RNAs (circRNAs) have emerged as potential key players in the onset and progression of various cancers. However, the specific roles and mechanisms of circRNAs in LUAD remain largely unexplored. Here, we aimed to elucidate the role of a particular novel circRNA, circLIMK1-005 (hsa_circ_0002690), in the pathogenesis of LUAD. Our study revealed that circLIMK1-005 was upregulated in LUAD and correlated with poor patient prognosis. Functionally, circLIMK1-005 significantly promoted LUAD cell proliferation and metastasis. Mechanistically, circLIMK1-005 elevated the expression of Cyclin D1 and CDK4 proteins, thereby activating CDK4 signaling. We further demonstrated that circLIMK1-005 promoted LUAD progression by binding with RPA1 protein and activating the CDK4 pathway. In vivo experiments corroborated these findings, confirming that the circLIMK1-005/RPA1/CDK4 axis contributed to LUAD progression and was associated with poor clinical outcomes. Our study revealed a novel mechanism of the circLIMK1-005/RPA1/CDK4 axis in LUAD progression, and highlighted that targeting circLIMK1-005 could represent a potential therapeutic strategy for patients with LUAD. Schematic diagram of hypothesis involved in the circLIMK1-005/RPA1/CDK4 axis in LUAD progression. Figure was created with BioGDP.com.